Gil Grissom and His Hidden Condition: Constructions of Hearing Loss and Deafness in CSI: Crime Scene Investigation - Foss, Katherine (Disability Studies Quarterly, 2009)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!– /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-parent:""; margin:0in; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; mso-bidi-font-weight:bold; @page Section1 size:8.5in 11.0in; margin:1.0in 1.25in 1.0in 1.25in; mso-header-margin:.5in; mso-footer-margin:.5in; mso-paper-source:0; div.Section1 page:Section1; –> <!–[if gte mso 10]> <![endif]–>Even with the increasing rate of hearing loss in adults, stigmas about hearing loss and old age continue to prevail. Film and television representations have traditionally ignored cases of hearing loss. When representations of hearing loss have appeared, they have presented negative portrayals, reinforcing stigmas about hearing loss. This study examines how CSI: Crime Scene Investigation portrays hearing loss and deafness. Through the main character, Gil Grissom, this program offers multiple understandings of hearing loss and deafness. Findings indicate that CSI presents hearing loss to be isolating and career damaging. Yet, also presented through Grissom’s character, deafness is conveyed not always as a functional limitation, but as one characteristic of a rich cultural community.